Using the visible thinking approach in reading for developing preparatory stage pupils$1 (Benglish persuasive writing skills /s - Ali Shaaban Taha Mohamed Ibrahim; Awatef Ali Sheir; Hissan Hassan El Shandaweily (2024)
This study aimed at investigating the effectiveness of using the visible thinking approach in teaching reading for developing English persuasive writing skills among preparatory stage pupils. The participants in this study were sixty pupils chosen from Sawada and Zaweyat Sultan preparatory schools, El Minya Governorate, during the first term of the 2023-2024 academic year. The study employed the quasi-experimental design in which two groups were divided into an experimental group (n=30) and a control one (n=30). The experimental group was taught using the visible thinking program whereas the control group was taught using the regular method. The instruments of the study were comprised of English persuasive writing skills checklist, a pre-post persuasive writing skills test and a scoring rubric. The test was administered to the two groups before and after implementing the visible thinking approach on the experimental group. The experimental group outperformed the control group in the persuasive writing skills as the findings of the study revealed that the experimental group students scored significantly higher than those in the control one on EFL persuasive writing skills test, mainly those of rhetoric composition of persuasive writing, language mechanics skills, vocabulary, organization and content. Consequently, the visible thinking approach proved to be an effective approach to develop persuasive writing if properly applied.
(3gOaJ GdOQGSI Edi JfejI egGQGJ GdcJGHI GdEbfGYjI HGddZI GdEfLdjRjI dOi JdGejP GdUa GdKGfj ef GdeQMdI GdEYOGOjI HGSJNOGe HQfGeL bGFe Ydi eONd GdJacjQ GdeQFj aj JOQjS GdbQGAI(B, (3h bO GSJNOe GdHGMK GdJUeje THg GdJLQjHj MjK JchfJ YjfI GdOQGSI ef SJjf WGdkHG h WGdHI Je GNJjGQge ef Hjf WdGH GdUa GdKGfj aj eOQSI ShGOI GdEYOGOjI GdeTJQcI (B- (3HEOGQI GdefjG GdJYdjejI(B, (3hPdc CKfGA GdaUd GdOQGSj GdChd ef GdYGe GdOQGSj (B2023/ 2024 (3e(B, (3hbO Je JbSje YjfI GdOQGSI Edi eLehYJjf(B: (3EMOGgeG JLQjHjI (B((3hYOOgG(B30 (3WGdkHG hWGdHI(B), (3hGdJj Je GdJOQjS dgG HGSJNOGe GdHQfGeL GdbGFe Ydi eONd GdJacjQ GdeQFj(B, (3hGdCNQi VGHWI (B((3hYOOgG(B30 (3WGdkHG hWGdHI(B), (3hGdJj Je GdJOQjS dgG HGSJNOGe GdWQjbI GdeYJGOI(B, (3hJVefJ COhGJ GdOQGSI bGFeI HegGQGJ GdcJGHI GdEbfGYjI(B, (3hGNJHGQ dbjGS egGQGJ GdcJGHI GdEbfGYjI(B, (3hCOGI dJbjje COGA GdWdGH aj GdGNJHGQ (B((Rubric, (3hbO Je JWHjb GNJHGQ egGQGJ GdcJGHI GdEbfGYjI HGddZI GdEfLdjRjI bHdkjG hHYOkjG Ydi eLehYJj GdOQGSI(B, (3hbO CTGQJ fJGFL GdJMdjd GdEMUGFj Edi hLhO aQhb PGJ OdGdI EMUGFjI Hjf eJhSW OQLGJ GdeLehYI GdJLQjHjI hGdeLehYI GdVGHWI aj GdJWHjb GdHYOj dGNJHGQ egGQGJ GdcJGHI GdEbfGYjI dUGdM GdeLehYI GdJLQjHjI YfO eSJhi OdGdI (B0.05(3; hHPdc abO CKHJJ GdfJGFL aYGdjI GSJNOGe GdHQfGeL GdbGFe Ydi GdJacjQ GdeQFj aj JfejI egGQGJ GdcJGHI GdEbfGYjI HGddZI GdEfLdjRjI(B.s
Thesis (Ph.D)-Cairo University, 2024.
Bibliography: pages 60-66.
Issues also as CD.
Text in English and abstract in Arabic & English.
Keywords: English Language; Visible thinking -- reading -- persuasive writing -- preparatory stage pupils